2024
DOI: 10.1055/s-0044-1782192
|View full text |Cite
|
Sign up to set email alerts
|

Case Report on Caries Assessment Using Intraoral Scanner Compared with Bitewing Radiographs

Bernard Siew,
Joachim Enax,
Frederic Meyer

Abstract: Dental caries remains one of the main reasons patients seeing their dentist. They either show up for preventive measures, diagnostics, or treatment of present caries lesions. To date, diagnostics are performed visually, supported by using bitewing radiographs. While radiographic diagnostics should only be performed on a biannual basis, and some caries process will not be seen with visual diagnostics, there remains a lack in regular checkups. Therefore, different technical applications can be used for regular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…This formulation was most effective in enhancing the mineral density of enamel and preventing the progression of early tooth decay. Due to this reason, a large number of analytical techniques, including micro-CT and scanning electron microscopy, were applied to prove the ability to remineralize [21,22]. The overall results evidenced the effectiveness of the hydroxyapatite-based toothpaste for the treatment of initial caries and the improvement of oral health and suggested that it could be recommended for inclusion in everyday dental practice to prevent caries and strengthen enamel structures [20].…”
mentioning
confidence: 99%
“…This formulation was most effective in enhancing the mineral density of enamel and preventing the progression of early tooth decay. Due to this reason, a large number of analytical techniques, including micro-CT and scanning electron microscopy, were applied to prove the ability to remineralize [21,22]. The overall results evidenced the effectiveness of the hydroxyapatite-based toothpaste for the treatment of initial caries and the improvement of oral health and suggested that it could be recommended for inclusion in everyday dental practice to prevent caries and strengthen enamel structures [20].…”
mentioning
confidence: 99%